Participant's Perspective on Arabic for Tourism Learning during the Covid-19 Pandemic - Maulani, Hikmah; Faqih, Ahmad (Journal of Tourism Education, 2021)
Abstract: The Covid-19 pandemic since 2019 has changed every aspect of online activities, including learning and tourism. The impact of the pandemic was felt directly in tourism Arabic learning as field observations are usually carried out, but the pandemic forced the closure of tourism. This study aims to obtain the perception of tourism Arabic learners during the COVID-19 pandemic and also found a description of the characteristics of learning during the pandemic. This study used an interview approach to obtain data, participants were students who were taking tourism Arabic lectures. The interview construct indicators were arranged with two themes, namely the adaptation of learners to online learning, the strategies of students doing assignments. The data is taken through whatssApp and google meet platforms, the analysis focuses on the answers from the compiled variable themes and the answers are analyzed by listening to the answers repeatedly. The results of the study show that there is an important role from the internal and external aspects of students in carrying out learning during the pandemic, this role is given by the environment, namely the condition of the family at home and their environment, lecturers, and also the concept of tasks and learning outcomes given by the lecturer.Keywords: Arabic, Pandemic, Tourism.